2020
DOI: 10.1080/0284186x.2020.1725111
|View full text |Cite
|
Sign up to set email alerts
|

Re-irradiation for recurrent rectal cancer – a single-center experience

Abstract: Background: There is no clear consensus on the use of re-irradiation (reRT) in the management of locally recurrent rectal cancer (LRRC). The aim of the present study was to investigate all reRT administered for rectal cancer at a large referral institution and to evaluate patient outcomes and toxicity. Material and methods: All patients with rectal cancer were identified who had received previous pelvic radiotherapy (RT) and underwent reRT during 2006-2016. Medical records and RT details of the primary tumor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…But the role of salvage treatments in patients with LR in the primary tumor bed after RT is controversial [ 21 ]. Re-irradiation has been successfully used in many recurrent tumors of various sites with the development of radiotherapy techniques, such as head and neck cancer [ 7 , 22 ], high grade glioma [ 23 ], lung cancer [ 24 ], intracranial germ-cell tumors [ 25 ], rectal cancer [ 26 , 27 ] and paediatric tumor [ 28 ] with encouraging results. Several small size retrospective studies reported the outcome of re-RT of LR for ESCC patients received RT [ 14 , 17 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…But the role of salvage treatments in patients with LR in the primary tumor bed after RT is controversial [ 21 ]. Re-irradiation has been successfully used in many recurrent tumors of various sites with the development of radiotherapy techniques, such as head and neck cancer [ 7 , 22 ], high grade glioma [ 23 ], lung cancer [ 24 ], intracranial germ-cell tumors [ 25 ], rectal cancer [ 26 , 27 ] and paediatric tumor [ 28 ] with encouraging results. Several small size retrospective studies reported the outcome of re-RT of LR for ESCC patients received RT [ 14 , 17 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of late GI toxicity was similar for XRT and PBT, 0–7%. However, a high incidence of Grade 3 or higher fistula formation was reported in the group of patients treated with concurrent chemotherapy and re-irradiation, who received a median dose of 50 Gy of XRT [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…[1,2,6,7] Currently, neoadjuvant chemoradiotherapy (nCRT) is an integral part of LRRC treatment. [2,[8][9][10][11][12][13][14][15][16] In radiotherapy naïve patients, nCRT is advised to downstage tumour volume and increase the likelihood of a radical resection (R0), which is the most important prognostic factor for survival. [1,4] Reirradiation in the setting of LRRC is feasible and safe, confirmed by low toxicity rates seen in the first prospective re-irradiation feasibility trial for LRRC performed by Valentini et al [17] Although re-irradiation does show encouraging results, the clinical benefit of re-irradiation is yet to be proven, as nCRT has not yet shown an effect on OS.…”
Section: Discussionmentioning
confidence: 99%